Answer:
Explanation:
Given
altitude of the Plane ![h=6\ miles](https://tex.z-dn.net/?f=h%3D6%5C%20miles)
When Airplane is
away
Distance is changing at the rate of ![\frac{\mathrm{d} s}{\mathrm{d} t}=290\ mph](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cmathrm%7Bd%7D%20s%7D%7B%5Cmathrm%7Bd%7D%20t%7D%3D290%5C%20mph)
From diagram we can write as
![h^2+x^2=s^2](https://tex.z-dn.net/?f=h%5E2%2Bx%5E2%3Ds%5E2)
differentiate above equation w.r.t time
![2h\frac{\mathrm{d} h}{\mathrm{d} t}+2x\frac{\mathrm{d} x}{\mathrm{d} t}=2s\frac{\mathrm{d} s}{\mathrm{d} t}](https://tex.z-dn.net/?f=2h%5Cfrac%7B%5Cmathrm%7Bd%7D%20h%7D%7B%5Cmathrm%7Bd%7D%20t%7D%2B2x%5Cfrac%7B%5Cmathrm%7Bd%7D%20x%7D%7B%5Cmathrm%7Bd%7D%20t%7D%3D2s%5Cfrac%7B%5Cmathrm%7Bd%7D%20s%7D%7B%5Cmathrm%7Bd%7D%20t%7D)
as altitude is not changing therefore ![\frac{\mathrm{d} h}{\mathrm{d} t}=0](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cmathrm%7Bd%7D%20h%7D%7B%5Cmathrm%7Bd%7D%20t%7D%3D0)
![0+x\frac{\mathrm{d} x}{\mathrm{d} t}=s\frac{\mathrm{d} s}{\mathrm{d} t}](https://tex.z-dn.net/?f=0%2Bx%5Cfrac%7B%5Cmathrm%7Bd%7D%20x%7D%7B%5Cmathrm%7Bd%7D%20t%7D%3Ds%5Cfrac%7B%5Cmathrm%7Bd%7D%20s%7D%7B%5Cmathrm%7Bd%7D%20t%7D)
at ![s=10\ miles\ and\ h=6\ miles](https://tex.z-dn.net/?f=s%3D10%5C%20miles%5C%20and%5C%20h%3D6%5C%20miles)
substitute the value we get ![x=\sqrt{10^2-6^2}=8\ miles](https://tex.z-dn.net/?f=x%3D%5Csqrt%7B10%5E2-6%5E2%7D%3D8%5C%20miles)
![8\times \frac{\mathrm{d} x}{\mathrm{d} t}=10\times 290](https://tex.z-dn.net/?f=8%5Ctimes%20%5Cfrac%7B%5Cmathrm%7Bd%7D%20x%7D%7B%5Cmathrm%7Bd%7D%20t%7D%3D10%5Ctimes%20290)
Here’s my work to your question. I used Newton’s Second Law and a kinematics equation to arrive at the answer.
The hiker followed the north trail a distance of two kilometers in thirty minutes is an example that provides a complete scientific description of an object in motion.
Answer:
x=?
dt=?
vi=23m/s
vf=0m/s (it stops)
d=0.25m/s^2
time =
vf=vi+d: 0=23m/s+(0.25m/s^2)t
t=92s
displacement=
vf^2=vi^2+2a(dx)
23^2=0^2+2(0.25m/s^2)x =-1058m
Explanation:
you can find time from vf = vi + a(Dt): 0 = 23 m/s + (0.25 m/s/s)t so t = 92 s and you can find the displacement from vf2 = vi2 + 2a(Dx) and find the answer in one step: 232 = 02 + 2(0.25 m/s/s)x so x = -1058 m
To do this you want to solve for one variable at a time. So we want to cancel out a variable. Lets cancel x. I will multiply the first equation by the number 4 to get 4y=4x-16.
Now lets solve equation 2 for y, giving
-3y=-4x+3 now add equation 1 to equation 2
Y =-13
Now plug that back in to either
-13=x-4
X=-9
So the answer is (-9,-13)